ICT in Rural Schools: realities and integration plans - Molina-Pacheco, Luis Eduardo; Mesa-Jiménez, Fredy Yesid (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The Government has offered to use technological means to strengthen a high-quality inclusive education system as a bastion of State policies on ICT, ensuring access for all students throughout the national territory. It is therefore necessary to analyze the impact of State policies on ICT in rural areas of the municipality of Tunja. To this end, facilities and barriers for access to communicational and computational infrastructure, the way teachers use the resources they have been given in specific situations, and the assimilation of these technologies in their pedagogical work are addressed. In that regard, this mixed methods research unveiled teachers’ latent needs and concerns. Furthermore, based on their experiences, a process for the integration of ICT into rural schools was developed, which includes planning, teacher training, availability and management of resources, maintenance and tracking of incentives.